KOMPARASI TEORI GESTALT DAN A.A.M DJELANTIK: STUDI KASUS DESAIN KOMUNIKASI VISUAL PADA IKLAN NUCIFERA - Suanda Maulana Usman; Muh Faisal; Meisar Ashari (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2022)
This research discusses the visual communication design contained in product advertisements from the Nucifera cafe by focusing on the shape, weight and presentation. The purpose of this research is to obtain information regarding Visual Communication Design in Nucifera Café Makassar Advertisements on Instagram Social Media. The object of this research is the advertising design at the Nucifera cafe which is handled by the marketing agency, Creanov. The data collection techniques used in this research are observation, interviews and documentation. The data analysis technique uses qualitative descriptive. The results of this research have four stages in the data collection process. The first stage is that the researcher collects data through observation, then interviews parties related to the research object and then documents the research object. The second stage is data reduction. After carrying out the first stage, data reduction is carried out and then supported by data collection, simplification and sorting. The third stage is data display, this data presentation is prepared after carrying out a series of stages, the form of data presentation is in the form of narrative text. The fourth stage is data conclusion, the final conclusion in the qualitative analysis process is carried out after the data has gone through several stages and then conclusions will be drawn.